2015
DOI: 10.1038/srep10639
|View full text |Cite
|
Sign up to set email alerts
|

Apology and forgiveness evolve to resolve failures in cooperative agreements

Abstract: Making agreements on how to behave has been shown to be an evolutionarily viable strategy in one-shot social dilemmas. However, in many situations agreements aim to establish long-term mutually beneficial interactions. Our analytical and numerical results reveal for the first time under which conditions revenge, apology and forgiveness can evolve and deal with mistakes within ongoing agreements in the context of the Iterated Prisoners Dilemma. We show that, when the agreement fails, participants prefer to take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 51 publications
1
53
0
Order By: Relevance
“…An AI system can apologize when such errors occur in order to build a long-term relationship with humans [23]. Theory shows that the apology needs to be delivered in a sincere way to be effective, such that it is costly to the producer of the system in material / financial terms [24]. • Emotions: Evidence from human-computer interaction studies [25] shows that AI/robots can be trusted more when they are capable of emotional expressions, e.g.…”
Section: Operationalizing Social Trust Through Game Theorymentioning
confidence: 99%
“…An AI system can apologize when such errors occur in order to build a long-term relationship with humans [23]. Theory shows that the apology needs to be delivered in a sincere way to be effective, such that it is costly to the producer of the system in material / financial terms [24]. • Emotions: Evidence from human-computer interaction studies [25] shows that AI/robots can be trusted more when they are capable of emotional expressions, e.g.…”
Section: Operationalizing Social Trust Through Game Theorymentioning
confidence: 99%
“…Studies of the effects of pre-commitment on the evolution of cooperation have recently started to report some results [4][5][6][7][8]. A common basic feature throughout these models is a commitment-compensation strategy to pay for setting up a commitment that guarantees cooperation and enforces compensation for its default.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, commitment is one of the most practical tools for maintaining social interactions and takes diverse forms (e.g., from a promise to a deposit and mortgage). Game-theoretical studies have shown that costly commitment can promote the evolution of cooperation in the context of the prisoner's dilemma [4][5][6][7][8]. This widely-studied commitment strategy works in a peer-to-peer fashion by allowing a personal proposer to ask his/her co-player to commit to cooperation, but also enforcing compensation if those who commit defect at a later stage.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in [31,34,43] the concept of network reciprocity was examined, and in [36] the conditions that lead to promotion of cooperation through indirect reciprocity in complex networks were explored. Other notable studies include the role of emotions [25,26] or punishment of defectors [2,24,37], dynamical link formation through indirect reciprocity [17], and even considering continuous action profiles [40,39].…”
Section: Introductionmentioning
confidence: 99%